2020
DOI: 10.2147/ott.s248085
|View full text |Cite
|
Sign up to set email alerts
|

<p>ADAMTS8 Inhibits Cell Proliferation and Invasion, and Induces Apoptosis in Breast Cancer</p>

Abstract: Introduction: A disintegrin and metallopeptidase with thrombospondin motifs (ADAMTSs), whose expression is dysregulated in various cancers, is implicated in cancer development. Herein, we aimed to investigate the functional role of ADAMTS8 in breast cancer (BC) and explore the underlying mechanisms. Methods: The protein expression of ADAMTS8 in BC cell lines and tumor tissues from BC patients was quantified by Western blot. ADAMTS8 overexpression was induced by transfection with pEZ-M90-ADAMTS8 plasmid using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…When utilizing the database from the CancerSEA, we found that low levels of ADAMTS8 enabled cancer cell invasion in glioblastoma multiforme (GBM). This invasion phenotypic change was consistent with breast cancer [ 33 ]. The GSEA using the TCGA cohort also suggested that ADAMTS8 was involved in poor survival in the Shedden lung cancer cohort.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…When utilizing the database from the CancerSEA, we found that low levels of ADAMTS8 enabled cancer cell invasion in glioblastoma multiforme (GBM). This invasion phenotypic change was consistent with breast cancer [ 33 ]. The GSEA using the TCGA cohort also suggested that ADAMTS8 was involved in poor survival in the Shedden lung cancer cohort.…”
Section: Discussionsupporting
confidence: 75%
“…ADAMTS8 belongs to the ADAMTS family, also known as METH-2, which play roles in a wide range of physiological processes, such as cell proliferation, apoptosis, migration, invasion, angiogenesis and extracellular matrix degradation [ 32 ]. It was initially recognized as an antiangiogenic factor in a variety of diseases, such as pulmonary artery hypertension [ 32 ] and different neoplastic diseases [ 33 , 34 ]. This study utilized bulky NGS to analyze the expression of different members of the ADAMTS family from eight paired normal and tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are no available reports examining the effect of Eimeria or other infections on the ADAMTS8 expression/activity in the avian intestine. This enzyme, a member of ADAMTS family, possesses anti-angiogenic properties ( Dunn et al, 2006 ) can inhibit cell proliferation, migration and invasion and promote apoptosis ( Zhao et al, 2018 ; Zhang et al, 2020 ), therefore, some alterations in ADAMTS8 mRNA expression observed in this study may be related to the modulation of mentioned processes in the intestinal sections of Eimeria -challenged chickens.…”
Section: Discussionmentioning
confidence: 81%
“…ADAMTS8 is one of the ADAMTS family proteins whose structure and function are similar to the matrix metalloproteinases (MMPs). [29] The ADAMTS genes participate in a wide range of biological processes such as extracellular matrix assembly and degradation, and ADAMTS8 has been proven to function as a tumor suppressor gene for BRCA. [30] DCAF12L2 is involved in a variety of cellular processes such as cell cycle progression and apoptosis, and it was only found to correlate with the microsatellite instability in colorectal cancer [31] but no research was reported about BRCA.…”
Section: Discussionmentioning
confidence: 99%